2018
DOI: 10.1371/journal.pone.0207793
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum 299V improves the microbiological quality of legume sprouts and effectively survives in these carriers during cold storage and in vitro digestion

Abstract: Probiotics improve consumers' health and additionally may positively influence the microbiological and organoleptic quality of food. In the study, legume sprouts were inoculated with Lactobacilllus plantarum 299V to produce a new functional product ensuring the growth and survival of the probiotic and high microbiological quality of the final product. Legume sprouts, which are an excellent source of nutrients, were proposed as alternative carriers for the probiotic. The key factors influencing the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
(45 reference statements)
0
25
0
Order By: Relevance
“…Lactobacillus plantarum, Torulaspora delbrueckii, Lactobacillus acidophilus 10 7 cfu/mL [92] Fermented oat flour Streptococcus thermophilus TH-4, Lactobacillus acidophilus LA-5 10 6 cfu/g [93] Fermented oat flour beverage Lactobacillus plantarum 10 14 cfu/mL [94] Legume sprouts Lactobacilllus plantarum 299V 10 9 cfu/mL [95] maize-based substrate…”
Section: Cereal Probiotic Product Probiotic Strains Viable Cell Countmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus plantarum, Torulaspora delbrueckii, Lactobacillus acidophilus 10 7 cfu/mL [92] Fermented oat flour Streptococcus thermophilus TH-4, Lactobacillus acidophilus LA-5 10 6 cfu/g [93] Fermented oat flour beverage Lactobacillus plantarum 10 14 cfu/mL [94] Legume sprouts Lactobacilllus plantarum 299V 10 9 cfu/mL [95] maize-based substrate…”
Section: Cereal Probiotic Product Probiotic Strains Viable Cell Countmentioning
confidence: 99%
“…The authors of [110] have also developed a novel multi-cereal-based fermented beverage using Lactobacillus helveticus KLDS1.9204. Study [95] inoculated legume sprouts with Lactobacilllus plantarum 299v in order to develop a new functional food. The sprouts that have been enriched with the probiotic culture, a lower mesophilic bacteria flora (especially lactic acid bacteria) was observed compared to the control sprouts (without probiotic).…”
Section: Cereal Probiotic Product Probiotic Strains Viable Cell Countmentioning
confidence: 99%
“…L. plantarum has been found to dominate early stages of a 4-stage of fermentation of mung bean as a base material for lu-doh-huang (Taiwanese herbal medicine) (Chao et al, 2013). In addition, a number of studies have documented the use of L. plantarum as a starter culture for mung bean-based fermentations (Wu et al, 2015;Landete et al, 2015;Gan et al, 2017;Świeca et al, 2018). Current work showed that the use of freezedried L. plantarum S20 starter was able to rapidly decrease pH of fermenting mung bean below pH 4.0 corresponding to maximum population of 9.3 log after 8 hrs.…”
Section: Fermentation Characteristics Of Freeze-dried Lactobacillus Pmentioning
confidence: 99%
“…The sprouts were cultivated as described previously Swieca et al (2018). The control (C) and probiotic-rich sprouts (LP) were produced by soaking the seeds in water or L. plantarum 299v water suspension (8.00 log 10 CFU/g of seeds) respectively.…”
Section: Sprouting Conditionsmentioning
confidence: 99%
“…Moreover, the Lb. plantarum population in this matrix was stable during the cold storage and successfully survived in the harmful conditions of the digestive tract in an in vitro model (Swieca et al ., ). Bacterial and fungal cell walls and/or the enzymes and lipids produced by the microorganisms can act as biotic elicitors (Matkowski, ); thus, it may be supposed that a probiotic or its metabolites can change plant metabolism, thereby modifying the consumer quality of resultant sprout‐based preparations.…”
Section: Introductionmentioning
confidence: 97%